PEMBERIAN UANG PESANGON MENURUT HUKUM ISLAM - Syaiful Achyar (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
Employment occurs after the employment agreement between workers and employers, which is an agreement in which the first party, workers, bind themselves to work for a wage on the other side, employers, which binds itself to employ workers with wages and severance pay in the event of layoffs. Severance pay provided by PT Mitra Saruta Indonesia to employees is the compensation to be paid by the company in the event of layoffs of workers. Severance can also be interpreted as a consequence or moral responsibility of the company, to ensure the survival of its employees for a certain period, after the layoffs. And Islam commands to mankind to help one another in terms of goodness and forbid mutual help in terms of ugliness. Islam also confirms an employer should be responsible for their workers. And it is the duty an employer to grant an employee before the worker dry sweat. And Islam also ordered a person who does the work agreement should fulfill the agreement and apply straight.